Pengaruh Faktor Budaya Dan Ketersediaan Sanitasi Terhadap Perilaku Stop Buang Air Besar Sembarangan (BABS) - Arif Eko Trilianto; Sulis Diana (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Open defecation remains a serious challenge in public health development, especially in rural areas of Indonesia. This study was conducted to analyze the influence of cultural factors and the availability of sanitation facilities on open defecation behavior in the working area of the Krejengan Probolinggo Community Health Center. This study used a cross-sectional design. The study population consisted of all married patients who visited the Krejengan Community Health Center in Probolinggo Regency, totaling 13,871 patients, with a sample of 100 people who met the inclusion criteria. Data were collected using questionnaires and analyzed using logistic regression. The results showed that, partially, cultural factors were also proven to have an effect, with a contribution of 8.9%, where negative culture increased the likelihood of open defecation by 2.972 times. The availability of sanitation facilities had the strongest influence, with a contribution of 9.2% and a prevalence ratio of 3.009. Multivariate analysis showed that only the availability of sanitation facilities variable was significantly influential when all variables were tested together. This confirms that sanitation infrastructure is a key enabling factor in changing open defecation behavior. These findings reinforce the importance of a structural approach to public health interventions, in which the provision of basic facilities must be a top priority before attempting to change behavior through education. Community- and culture-based interventions remain necessary to support the sustainability of the Stop Open Defecation program.